2010
DOI: 10.1097/hjh.0b013e328336c8e9
|View full text |Cite
|
Sign up to set email alerts
|

Pulse waveform characteristics predict cardiovascular events and mortality in patients undergoing coronary angiography

Abstract: The study provides evidence that pulse waveform characteristics consistently and independently predict cardiovascular events in coronary patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 30 publications
(40 reference statements)
2
60
0
2
Order By: Relevance
“…[38][39][40] In this context, our findings are in accordance with the artery size hypothesis, according to which atherosclerosis is widespread throughout the arterial tree, but it is clinically manifest initially as ED because the same amount of atherosclerotic burden compromises flow first through the smaller lumen of the penile arteries. 7,41 However, it should be noted that arterial stiffness is also a predictor of acute coronary events, 38 which in their majority occur in the presence of nonobstructive atherosclerotic disease.…”
Section: Discussionsupporting
confidence: 89%
“…[38][39][40] In this context, our findings are in accordance with the artery size hypothesis, according to which atherosclerosis is widespread throughout the arterial tree, but it is clinically manifest initially as ED because the same amount of atherosclerotic burden compromises flow first through the smaller lumen of the penile arteries. 7,41 However, it should be noted that arterial stiffness is also a predictor of acute coronary events, 38 which in their majority occur in the presence of nonobstructive atherosclerotic disease.…”
Section: Discussionsupporting
confidence: 89%
“…Aortic pressure augmentation due to wave reflection could cause myocardial ischemia by increasing the left ventricular wasted effort and ejection duration, even in the absence of overt coronary stenosis (Nichols et al 2013). As summarized in previous reviews (Vlachopoulos et al 2010;Hashimoto and Ito 2012), several prospective studies conducted on coronary artery disease patients have demonstrated that the central pulse pressure and augmentation index predict future cardiovascular events, and the predictive ability is superior to (or independent of) the brachial pressure (Chirinos et al 2005;Weber et al 2005Weber et al , 2010Jankowski et al 2008).…”
Section: Central Hemodynamics and Heartmentioning
confidence: 99%
“…Central hemodynamic properties may be monitored with accuracy [4] and precision [5] using pulse wave analysis (PWA). Typically, the pressure waveform is non-invasively monitored at a peripheral site, and using a generalized transfer function, a corresponding aortic arterial waveform can be generated [6,7].…”
Section: Introductionmentioning
confidence: 99%